The Evolution of Monoclonal Gammopathy of Undetermined Significance in Kidney Transplant Recipients. Issue 10 (October 2019) - Gagnon, Marie-France; Cardinal, Héloïse; Emond, Jean-Pierre; Latour, Mathieu; Lemieux, Bernard
Abstract : Background: It is unclear if immunosuppression increases the likelihood of malignant transformation of monoclonal gammopathy of undetermined significance (MGUS) and whether adverse renal outcomes in kidney transplant recipients with MGUS are more frequent. Methods: We performed a retrospective cohort study of kidney transplant recipients at the Centre Hospitalier de l'Université de Montréal between 2000 and 2016. Results: Among 755 study participants, 13 (1.7%) were found to have MGUS before transplant. Two evolved to smoldering multiple myeloma and 2 presented paraprotein-induced allograft injury from light chain deposition disease. Forty-six patients developed posttransplant MGUS (2.5% 5-y cumulative incidence) of which 1 progressed to multiple myeloma and 1 experienced kidney allograft loss from light chain deposition disease. None of the patients with a malignant transformation or paraprotein-induced renal disease after transplantation had had a systematic workup before transplantation to exclude hematologic malignancies and paraprotein-related kidney injury. Nine posttransplant MGUS (21%) were transient. Multivariable analysis revealed that age at transplant (hazard ratio 1.05 per 1-y increase, 95% confidence intervals, 1.02-1.08) and prior cytomegalovirus infection (hazard ratio 2.22, 95% confidence intervals, 1.07-4.58) were associated with the development of MGUS after transplantation. Of 7 posttransplant lymphoproliferative disorders, none were preceded by MGUS. Conclusions: Our results suggest that the identification of MGUS in a transplant candidate should lead to further investigations to exclude a plasma cell neoplasm and monoclonal gammopathy of renal significance before transplantation. MGUS arising after transplantation appears to carry a favorable evolution.